ChemInform Abstract: Molecularly Imprinted Polymer Nanoparticles in Chemical Sensing ‐ Synthesis, Characterization and Application. Issue 9 (March 2015) - Wackerlig, Judith; Lieberzeit, Peter A.
Abstract Review: 149 refs.